Anthropometric and fitness characteristics of elite australian female water polo players - Tan, F. H. Y.; Polglaze, T.; Dawson, B.; Cox, G. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to investigate the anthropometric and fitness characteristics of elite female water polo players and examine the differences between players of different competition levels (national and international) and playing positions (center and perimeter). Twenty-six female water polo players (National League, n = 12, and National Squad, n = 14) underwent measurements of standard anthropometry (height, body mass, and sum of 7 skinfolds), lower-body muscular power (in-water vertical jump), speed (10-m maximal sprint swim), and aerobic fitness (multistage shuttle swim test). No goalkeepers were involved. The National Squad players were taller (173.7 ± 5.5 vs. 169.6 ± 4.4 cm; p < 0.05) and heavier (74.6 ± 8.0 vs. 65.8 ± 8.4 kg; p < 0.05) and had better jumping (139.0 ± 7.0 vs. 129.7 ± 4.6 cm; p < 0.001), sprinting (5.96 ± 0.21 vs. 6.26 ± 0.34 seconds; p < 0.05), and endurance swimming abilities (652 ± 84 vs. 449 ± 124 m; p < 0.001) compared with the National League players. Perimeter players had lower-body mass (70.2 ± 3.8 vs. 82.5 ± 7.4 kg; p < 0.001) and skinfold levels (88.7 ± 14.1 vs. 118.6 ± 22.2 mm; p < 0.01) and better sprinting (5.88 ± 0.19 vs. 6.10 ± 0.19 seconds; effect size [ES] = 1.16, p > 0.05) and endurance swimming abilities (678 ± 65 vs. 606 ± 102 m; ES = 0.84, p > 0.05) compared with center players. These findings demonstrate that anthropometric and fitness characteristics can discriminate between players of different competition levels and playing positions. These water polo-specific field tests may assist coaches in profiling players and evaluating adaptations to training.